Pete the Cat : rocking field day - Dean, Kim, 1969-; Dean, James, 1957- (2021)
Anticipating an extra-groovy field day, Pete the cat and his friends Callie, Grumpy Toad, and Gus compete for medals in activities ranging from a water-balloon toss to a three-legged race
Illustrations were rendered using watercolor, acrylic and ink
Marantz copy has the original dust jacket
Ages 4-8
Guided reading level J
Marantz copy has original publisher's binding: paper covered boards with illustrations on front and back covers
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Outdoor recreation -- Juvenile fiction; Contests -- Juvenile fiction; Easy readers; Juvenile works; Fiction; Humorous fiction; Animal fiction; Sports fiction; Picture books; Paper case bindings; Illustrated case bindings